Phylogenetics and biogeography of the relhanioid paper-daisy lineage (Asteraceae: Gnaphalieae) : palaeoenvironmental evolution, migration and speciation in southern Africa and the greater Afrotemperate regions - Bentley, Joanne (Department of Biological Sciences, 2014)
Includes bibliographical references.